Plurilingualism and Curriculum Design: Toward a Synergic Vision. Issue 3 (16th August 2013) - Piccardo, Enrica
<x xml:space="preserve">Abstract</x> Contemporary globalized society is characterized by mobility and change, two phenomena that have a direct impact on the broad linguistic landscape. Language proficiency is no longer seen as a monolithic phenomenon that occurs independently of the linguistic repertoires and trajectories of learners and teachers, but rather shaped by uneven and ever‐changing competences, both linguistic and cultural. In the European context, research conducted over the past 20 years in multilingual realities of local communities and societies has brought to the forefront the notion of plurilingualism, which is opening up new perspectives in language education. In North American academia, the paradigm shift from linguistic homogeneity and purism to heteroglossic and plurilingual competence in applied linguistics has been observed in the emergence of such concepts as disinventing languages, translanguaging, and code‐meshing. Starting from a historical perspective, this article examines the shared principles upon which such innovative understandings of linguistic competence are based. In particular, it investigates the specificity of plurilingualism as an individual characteristic clearly distinct from multilingualism in the light of different theoretical lenses. The author discusses the potential of such vision together with its implications. Finally, this article offers pedagogical implications for English language education in the North American context, and suggests ways to investigate the new active role that English language learners and teachers can adopt in shaping their process of learning English.